A rare case of persistent hyperkalaemia. (November 2021) - Lewis, Thomas; Roberts, Gareth; Zouwail, Soha
Hyperkalaemia is a common biochemical finding that can allude to preanalytical or truly pathological causes. Here, we present a case of a 41-year-old female patient who has regularly presented with incidences of isolated hyperkalaemia since 2012, with otherwise normal renal function and no other associated symptoms. Investigations into the patient's family history revealed similar biochemical findings in her brother and eldest son. Familial causes of hyperkalaemia were investigated and an eventual diagnosis of pseudo-hypoaldosteronism type 2C was established. This is a rare congenital renal tubular disorder – also known as Gordon syndrome – that can cause a characteristic triad of symptoms that include hyperkalaemia, metabolic acidosis and hypertension. The presence and severity of each of these symptoms is dependent upon the disease-causing mutation that occurs in WNK4, WNK1, CUL3 or KLHL3 genes. These mutations alter the regulation of sodium/chloride co-transporter (NCC) expression on the luminal membrane of the principal cells of the distal convoluted tubule, disrupting normal homeostatic regulation of electrolyte reabsorption and excretion. The resolution for treating this condition is the administration of a thiazide diuretic, which directly counteracts the effects of NCC co-transporter overexpression and consequently aims to resolve the symptoms that arise as a result of this aberrant signalling. The case described here uniquely presents an extremely rare pathogenic variant in the conserved acidic motif of WNK1 resulting in a clear electrolyte phenotype with no hypertension.